2019
DOI: 10.29138/prd.v1i1.99
|View full text |Cite
|
Sign up to set email alerts
|

ELancing Motivation on Sribulancer, an Evidence from Indonesia

Abstract: eLancing is a growing trend in Indonesia. More and more people opt to become eLancers due to the job and time flexibility. This paper aims to explore further the motivational factors for Indonesian eLancers to work in Sribulancer, an online platform for freelancers. Using qualitative approach, 200 semi structured interviews were conducted to eLancers in Sribulancer.com. The result exhibited eight (8) primary motivations of eLancing such as work-family balance, flexibility and autonomy, economic incentives, ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…In addition, Riyono and Usman (2022) also claimed that most freelancers decided to work full-time in the freelancer IT sector on the grounds of flexibility and adequate time to spend with family members and a degree of freedom to make decisions, namely freedom over decision-making. Wulandari et al (2019) indicated that flexibility played an essential role in decision-making in opting for the Sribulancer platform. The flexibility factors will undoubtedly come to mind when considering employment in the gig economy in comparison to traditional work settings.…”
Section: Workloadmentioning
confidence: 99%
“…In addition, Riyono and Usman (2022) also claimed that most freelancers decided to work full-time in the freelancer IT sector on the grounds of flexibility and adequate time to spend with family members and a degree of freedom to make decisions, namely freedom over decision-making. Wulandari et al (2019) indicated that flexibility played an essential role in decision-making in opting for the Sribulancer platform. The flexibility factors will undoubtedly come to mind when considering employment in the gig economy in comparison to traditional work settings.…”
Section: Workloadmentioning
confidence: 99%
“…The difference between freelance developers and traditional developers are well noted in [11]. In terms of measuring freelance developer performance, achievement goals need to be included; these are defined as proficiency-relevant goals that an individual would make in relation to their competency [22]. Achievement goals are important in determining the career success and growth of a freelance developer, as they are self-employed individuals, compared to traditional developers who usually have a predetermined key performance indicator set by the attached organization.…”
Section: Achievement Goalsmentioning
confidence: 99%